ANALISA ELECTRODE CONSUMABLE TYPE OK AUTROD 12.10 PENGELASAN SUBMERGED ARC WELDING PADA BLOK-BLOK KAPAL DCV 18500 DWT DI PT. JASA MARINA INDAH UNIT II SEMARANG - Jatmiko, Sukanto (Department of Naval Architecture - Diponegoro University, 2010)
In this globalization era technological advances growed very fast. In shipping industry of development process shipbuilding of principal feedstock to used steel plate, with construction tacking on using welder method.In this research purpose of lifted is know number of requirement (consumable) electrode for welder SAW at block-block ship DCV 18500 DWT in PT. Jasa Marina Indah Semarang.At this experiment specimen applied is low carbon steel of type ST 42 with thickness of 12, 13, 14, 17, 19 dan 24 mm. Research is done by the way of making specimen at every plate thickness. Then is done path measurement of length, used electrode length, and weight flux applied at the welder.From result of gauging and data calculation welder at block DB 5(p/c/s), SS5A(p/s), SS 5B(p/s), UD 5C, and TB 102 (p/c/s) will be known number of electrodes applied in welder SAW and number of flux used.